Endogenous redistributive cycles: an overlapping generations approach to social conflict and cyclical growth - Christiane Clemens; Maik Heinemann (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2005)
This paper discusses the emergence of endogenous redistributive cycles in a stochastic growth model with incomplete asset markets and heterogeneous agents, where agents vote on the degree of progressivity in the tax.transfer.scheme. The model draws from Bénabou (1996) and ties the bias in the distribution of political power to the degree of inequality in the society, thereby triggering redistributive cycles which then give rise to a nonlinear, cyclical pattern of savings rates, growth and inequality over time.
Keywords: D31; E62; O41; P16; 330; Einkommensumverteilung; Politischer Konjunkturzyklus; Stochastisches Wachstumsmodell; Chaostheorie; Theorie; Overlapping Generations